Some features of Antarctic deep-sea squid (ADSS) biology Mesonychoteuthis hamiltoni, Robson, 1925 - V. L. Yukhov (Ukrainian Antarctic Journal, 2013)
ADSS research results according to investigation of the diet of sperm whales in Antarctica for the period of 1967-1979 are generalized in the work. ADSS information retains its value and relevance. ADSS is one of the most massive squid in Antarctica. In December – March it occurs in the area of 60-70°S within the temperature range of -1,9°C to +2,0°C with the frequency of occurrence maximum from -0,9°C to 0°C. Length frequency of individuals of both sexes with mantle length of 80-240 cm is equal to 86% of occurrence. ADSS adults inhabit vertically mesopelagic (200-799 m) and bathypelagic (700-2000 m) ocean zones. ADSS occurs together with Antarctic toothfish. During the period of November – April ADSS female gonads are on the II-III maturity stage. Most likely the spawning is not one-time and takes place at the end of winter – early spring. ADSS composition of food in open Antarctic waters is monotonous. From 849 exposed stomachs only 107 (12,6%) have contained residues of victims, probably, of Myctophidae family. Mantle meat yield is up to 65,7%. In spite of availability of NH4 group, squid meat has a delicate nice taste that makes it possible to regard ADSS as a fishery object in perspective.